2022
DOI: 10.1007/s42114-022-00417-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electromagnetic wave absorption of engineered epoxy nanocomposites with the assistance of polyaniline fillers

Abstract: In this work, the engineered polyaniline (PANI)/epoxy composites reinforced with PANI-M (physical mixture of PANI spheres and fibers) exhibit significantly enhanced electromagnetic wave absorption performance and mechanical property. Due to the synergistic effect of PANI fillers with different geometries, the reflection loss of 10.0 wt% PANI-M/epoxy could reach − 36.8 dB at 17.7 GHz. Meanwhile, the mechanical properties (including tensile strength, toughness, and flexural strength) of PANI/epoxy were systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The much higher ε′ and ε″ values of the pristine MXene nanosheets compared to those of the MXene bowls indicated that the bowl‐like structures endowed the MXenes with moderate permittivity, facilitating a well‐matched impedance (Figures S18 and S19, Supporting Information). [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The much higher ε′ and ε″ values of the pristine MXene nanosheets compared to those of the MXene bowls indicated that the bowl‐like structures endowed the MXenes with moderate permittivity, facilitating a well‐matched impedance (Figures S18 and S19, Supporting Information). [ 59 ]…”
Section: Resultsmentioning
confidence: 99%
“…The much higher ε′ and ε″ values of the pristine MXene nanosheets compared to those of the MXene bowls indicated that the bowl-like structures endowed the MXenes with moderate permittivity, facilitating a well-matched impedance (Figures S18 and S19, Supporting Information). [59] The dielectric loss tangent (tan δ ε ), defined as ε″/ε′, represents the ability to convert EM energy into heat energy by the attenuation of time-varying EM field-induced currents in conducting networks. [60] The tan δ ε -f curve of M-2 and M-4 showed significant resonance peaks, indicating the existence of polarization relaxations (Figure S20a, Supporting Information).…”
Section: Electromagnetic Wave Absorption Of the Hollow Mxene Bowlsmentioning
confidence: 99%
“…This might be related to the quality of the dispersion of the nanoflakes in the PVDF matrix. Generally, the achievement of high-quality dispersion of the nanofiller in a polymer matrix is a challenging issue, especially at higher loadings. , Although the processing conditions are an important parameter that could impact on the dispersion quality of the nanoflakes in composites, at the same ensured processing conditions, compatibility between the polymer and the nanofiller plays a decisive role in reducing the risk of nanofiller aggregation and thus enhancing the dispersion quality. Better nanofiller dispersion could not only reduce the stress concentration sites in the composite but also improve the polymer–filler interactions and enhance the capability of the composite to withstand higher stress before failure.…”
Section: Resultsmentioning
confidence: 99%
“…For PANI/MXene/nylon films, the EMI SE performance and power coefficient with opposite incident direction of EM wave are depicted in Figure S14 and Figure S15. When the EM waves are first incident on PANI layer, the A value is decreasing and always less than the R value, indicating that when the EM waves arrive at the surface of object, the reflection is inferior to the absorption due to the impedance mismatch. , When the EM waves are first incident on MXene layer, the EMI SE performance is similar to that on PANI layer; however, the larger R value indicates a better reflection ability of MXene layer. Also, it means a reliable reflection-dominated shielding mechanism no matter from which side the EM waves are incident.…”
Section: Resultsmentioning
confidence: 99%
“…50,51 When the EM waves are first incident on MXene layer, the EMI SE performance is similar to that on PANI layer; however, the larger R value indicates a better reflection ability of MXene layer. Also, it means a reliable reflection-dominated shielding mechanism no matter from which side the EM waves are incident.…”
mentioning
confidence: 99%